MULTICULTURALISM AMID SOCIETAL AND CULTURAL PLURALITY IN INDONESIA - Saryono, Prof Djoko; Amri, Misbahul (Jurnal Pembelajaran Sastra, 2022)
Plurality, diversity, and heterogeneity as well as multiversity of Indonesian society and culture were and still are factual reality in Indonesia, even before this nation-state was founded in 1945. Therefore, in order to live together peacefully and full of equal understanding between one to the others, it is a must to avoid monolithic, homogeneous and uniform policies as far as possible. To achieve this goal, we have to be able to build and realize some form of synergy by way of understanding, tolerance, togetherness, and cooperation each other. Hence, learning to live together, multicultural awareness, and multicultural behaviors are prerequisite to pass over cross-cultural understanding and cross-cultural learning. This, then, insists the importance of multicultural education and here is the site where Indonesian universities have to play their role. The following article will illustrate that society and culture are natural or given but they are man made and enculturised within the groups to live their lives.